1998
DOI: 10.1046/j.1365-2265.1998.00361.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypertension in acromegalic patients: clinical measurement versus 24-hour ambulatory blood pressure monitoring

Abstract: Ambulatory blood-pressure monitoring indicated a lower prevalence of hypertension in acromegalic patients then usually reported, suggesting that the role of hypertension in the pathogenesis of acromegalic cardiomyopathy is commonly overestimated. We propose that ambulatory blood-pressure monitoring should be routinely proposed in acromegalics with high or borderline clinical blood pressure values although it is not useful in patients defined normotensive according to repeated clinical measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 23 publications
2
20
0
3
Order By: Relevance
“…23 In addition, there are data to suggest that hypertensive patients who are salt sensitive are more likely to be non-dippers than patients who are salt resistant. 24 Our results are in contrast with those observed by Minniti et al, 7 who in only one out of seven acromegalics with hypertension observed the absence of the physiological night-time decrease of BP, but they are in agreement with those observed by Terzolo et al, 8 who in five out of seven defined as hypertensives by ABPM found a non-dipper, altered night-day ratio for BP. In essential hypertensives it was observed that the ratio of fasting insulin to glucose was higher in non-dippers.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…23 In addition, there are data to suggest that hypertensive patients who are salt sensitive are more likely to be non-dippers than patients who are salt resistant. 24 Our results are in contrast with those observed by Minniti et al, 7 who in only one out of seven acromegalics with hypertension observed the absence of the physiological night-time decrease of BP, but they are in agreement with those observed by Terzolo et al, 8 who in five out of seven defined as hypertensives by ABPM found a non-dipper, altered night-day ratio for BP. In essential hypertensives it was observed that the ratio of fasting insulin to glucose was higher in non-dippers.…”
Section: Discussionsupporting
confidence: 66%
“…5,6 There is no direct relationship between the degree of cardiomegaly and the level of circulating growth hormone (GH). 5,6 With only two exceptions 7,8 hypertension in acromegalyc patients was studied with sphygmomanometric methods and hence, there is scanty information on the circadian variations in blood pressure (BP) and heart rate (HR). Moreover, the available results are contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…Minniti et al [7] studied 40 patients with active acromegaly. They also found a higher prevalence of hypertension by office measurements than ABPM and a positive correlation between age and 24-h SBP, without association between BP levels and GH or IGF-1.…”
Section: Blood Pressure In Acromegalymentioning
confidence: 99%
“…However, few studies have measured the prevalence of hypertension using 24-h ambulatory blood pressure monitoring (ABPM) [4][5][6][7]. Moreover, when the clinical measurements were compared with ABPM, it has been suggested that office measurements overestimate the prevalence of hypertension in patients with acromegaly [5].…”
Section: Introductionmentioning
confidence: 99%
“…Arterial blood pressure (systolic and diastolic) is higher with loss of normal daily circadian variability (Terzolo et al, 1999). Hypertension was reported in approximately one third of patients who had acromegaly (Pietrobelli et al, 2001;Minniti et al, 1998). Insulin resistance and diabetes mellitus occur as a result of direct anti-insulin effects of GH (Coculescu et al, 2007;Kasayama et al, 2000).…”
Section: Clinical Features Of Acromegalymentioning
confidence: 99%